Financial technologies and the effectiveness of monetary policy transmission - Iftekhar Hasan; Boreum Kwak; Xiang Li (Halle Institute for Economic Research (IWH), 2023)
This study investigates whether and how financial technologies (FinTech) influence the effectiveness of monetary policy transmission. We use an interacted panel vector autoregression model to explore how the effects of monetary policy shocks change with regional-level FinTech adoption. Results indicate that FinTech adoption generally mitigates the transmission of monetary policy to real GDP, consumer prices, bank loans, and housing prices, with the most significant impact observed in the weakened transmission to bank loan growth. The relaxed financial con straints, regulatory arbitrage, and intensified competition are the possible me chanisms underlying the mitigated transmission.
Keywords: C32; E52; G21; G23; 330; financial technology; interacted panel VAR; monetary policy